A Study of Major Syntactical, Written and Oral Communication Differences between British and American English: Exploring the Variations between British and American English (Journal of Advances and Scholarly Researches in Allied Education, 2017)
As a universal language, English provides the opportunities for people from different countries to communicate conveniently. As language is changeable, English also develops constantly and produces many kinds of varieties among which, British English and American English are the two important ones. They have great differences in vocabulary, pronunciation grammar, and other aspects. The paper focuses on lexical differences between British English and American English.This study talks about syntactic, written and oral communication distinctions in British and American English. It points at talking about the distinctions from an evaluative purpose of view. It is a welcome to the scientists to view and take a shot at American English contrastingly as opposed to passing by the general origination of improvement. Dialect has dependably been valid and solid wellspring of recognizable proof. The same is accurate to the American English.The aim of this study is to underscore the major contrasts between British and American English both in composed and oral correspondence. Besides, this research is planned to build the universally adored in concentrating on one or an alternate, and to be cognizant which English they talk and how effectively or inaccurately they talk it, contingent upon the reason for their uttering. As English has come to be more than a pattern these days it turned out to be to be extremely intriguing the investigation of what sort of English we talk, what sort of English we hear around us, in films, while listening to music or even while visiting on the web.